Ethical Interactions in the Household in Surah An-Nur Verses 58-61 (Analysis of Ibn Kathir's Tafsir) - Iqbal, Achmad Ichsanul Alaudin (Universitas Muhammadiyah Surakarta, 2023)
As Muslims, we make the Qur'an a guideline for life. The Qur'an also discusses morals or good manners for visiting other people's homes. The reason is that many people today do not understand the etiquette of visiting properly. In Islamic teachings, Surah An-Nur verses 58-61 provide ethical guidelines in social and household interactions. These verses emphasize the importance of manners when entering a house, dressing modestly, and maintaining privacy in social interactions. This study aims to analyze the ethical values contained in the interpretation of Surah An-Nur verses 58-61 related to household interactions according to various scholars and commentators. This study analyzes classical and contemporary interpretations that explain these verses. Various interpretations, such as Ibn Kathir, al-Jalalain, and others, are used to understand the context, meaning, and practical application of the ethical values contained in these verses. Verse 58 emphasizes the manners of entering a house and upholding privacy. Verse 59 discusses the importance of dressing modestly to maintain purity and respect oneself. Verses 60 and 61 highlight the prohibitions on privacy and emphasize that these rules are instructions from Allah to regulate human relationships in a dignified manner. This study illustrates the importance of ethics in household relationships, highlighting the values contained in Surah An-Nur verses 58-61 and their relevance in social and family life.